Assessment of vascular-platelet hemostasis in patients with hemorrhagic forms of erysipelas - R. I. Ratnikova; T. A. Dubovikova (Журнал инфектологии, 2014)
The article presents the results of the research of vascular-platelet hemostasis in dynamics with the patients with hemorrhagic forms of erysipelas. Found an increase platelet aggregation in the background of a decrease in the total number of the given clinical forms of the disease. The greatest changes were typical for bullosa hemorrhagic process in the study of collagen-induced aggregation. Also revealed the presence of endothelial dysfunction by increased activity of von Willebrand factor.